Education Inspectorate in LOMLOE Draft, amendments and law. The significance of changes - Montero Alcaide, Antonio (Avances en Supervisión Educativa, 2021)
The Spanish educational system is experiencing new changes since a new Law of Education (LOMLOE,2020) has been approved, which modifies the previous one. Although the first draft did not introduce any significant variations regarding the Education Inspectorate, the work done by the Parliament leading to pass the law did add substantial amendments to it. This article focuses on these changes and aims to explain how relevant and important they are. To achieve this, the author will analyze the content of the numerous amendments that were submitted to discussion and the significance of the modifications finally incorporated to the new law. From here, the reader may comprehend the particularities and singularities involving the passing of a new reform in education as well as the relevance of the changes, adjustments and development of key elements integrated in the inspection and supervision tasks.